Ius Curia Novit and Malay Customary Values as Determinants of Substantive Justice in Indonesian Courts: A Convergent Mixed-Methods Study - Indrayani; Henry Halim; Machdaliza; Aziwarti; Martimbang Simbolon (HM Publisher, 2023)
The principle of Ius Curia Novit compels judges to accept and decide cases even when statutory law is absent, ambiguous, or incomplete, yet in jurisdictions with strong customary traditions strict legal positivism often yields procedurally correct but substantively unjust outcomes. This study examined how judicial activation of Ius Curia Novit and the integration of Malay customary values relate to perceived substantive justice. A convergent parallel mixed-methods design integrated a qualitative strand (interviews and verdict analysis from a District Court and a Religious Court in Riau Province, Indonesia) with a cross-sectional survey of 184 legal practitioners using four validated multi-item scales (Cronbach's α 0.835-0.872). Data were analysed with Pearson correlation, Welch's t-tests, one-way ANOVA, and multiple linear regression, reporting effect sizes and 95% confidence intervals. Ius Curia Novit activation (β = 0.418, 95% CI 0.284-0.529, p < 0.001) and customary-law integration (β = 0.281, 95% CI 0.150-0.381, p < 0.001) were the strongest positive predictors of perceived substantive justice, whereas legal-positivism orientation was a negative predictor (β = −0.227, p < 0.001); the model explained 49.2% of the variance (F(5,178) = 34.46, p < 0.001). Customary integration was higher in the Religious Court than the District Court (d = 0.63, p < 0.001) and differed by practitioner role (η² = 0.156, p < 0.001). Judicial discovery and disciplined incorporation of local wisdom jointly transform the judge from a mouthpiece of the law into an architect of substantive justice, informing judicial training and customary-law recognition policy.